The Risk Factors Determining Anemia and Its Effect among Senior High School Students in Samarinda, Indonesia - Umi Kalsum; Badar Badar (Humanistic Network for Science and Technology (HNST), 2021)
Anemia in female teenagers need to be prevented. If it happens, it needs to be treated immediately because it can disturb concentration leading to various effects such as decreased educational achievement at school, risk of being attacked by infectious disease, decreased fitness and productivity as well as the risk of having anemia among the pregnant mothers. This study aimed to know the relationship between the hemoglobin level and Body Mass Index, physical fitness, menstrual cycle, educational achievement, and infectious diseases history on Senior High School students. This research was conducted quantitatively through an analytical study ad cross-sectional design. The sample size of this study were 97 students who are met the inclusion criteria. Risk factors of anemia on adolescence were Body Mass Index (p-value: 0.0001), menstrual cycle (p-value: 0.0001), and infectious disease history (p-value: 0.005). Anemia itself had a relationship to physical fitness (OR: 7.98 with 95% CI: 2.64 – 24.13), and have no relationship to educational achievement on students (OR: 1.94 with 95% CI: 0.22 – 17.02). Body Mass Index, menstrual cycle, and infectious disease history are the risk factors for anemia on this study. Meanwhile, anemia can contribute to changes in physical fitness. Keywords: anemia; menstrual cycle; body mass index; physical fitness